EFFECTIVENESS OF CROSS-PROTECTIVE RECOMBINANT INFLUENZA VACCINE BASED ON CONSERVED EPITOPES OF VIRAL PROTEINS М2 AND HEMAGGLUTININ - L. A. Stepanova; M. A. Shuklina; E. A. Blokhina; R. Y. Kotlyarov; A. A. Kovaleva; N. V. Ravin; L. M. Tsybalova (Журнал инфектологии)
The influenza virus is the most unique in the level of variability of antigenic and biological properties. Because of constant mutations into genes coding surface viral proteins, in modern vaccines it is necessary to replace 1–2 virus components annually. Traditional influenza vaccines are the strain – specific and have limited efficiency in prevention of new strains of influenza viruses. In this regard, creation of influenza vaccines based on conserved determinants of viral proteins with broad spectrum protection and the short period of production is one of priority tasks which decision will lead to real control of an influenza infection. A current trend in the design of universal flu vaccines is the construction of recombinant proteins based the combination of conserved viral proteins or peptides. The goals of this study: to develop the candidate recombinant flu vaccine based on the two conserved influenza proteins (М2 and НА); to investigate immune response; and to measure the protection activity in an animal model. Results: In this study we investigated the humoral and T-cell response in mice after intranasal immunization with recombinant proteins (Flg-4M2ehs and Flg-HA2-2-4M2ehs). Both proteins induce a robust M2e-specific humoral and CD4+ T-cell response in mice lung. The recombinant protein with two target antigens (M2e and HA2) induces virusspecific CD4+ and CD8+ T-cell response and full protection (100% survival) of mice from lethal challenge human and avian influenza viruses A (A/H3N2, A/H2N2, A/H5N1). In mice immunized with Flg-4M2ehs, the survival after lethal challenge was 60–75%. Conclusion: Our results show an essential role of a conserved fragment of the HA2 in the formation of protective T-cell response and protection of mice from lethal challenge with influenza viruses A of various subtypes. The prospects of the development of vaccine formulation based on two conserved antigenic determinants of influenza virus A are shown.